Clinical and neuropsychological follow up at 12 months in patients with complicated Parkinson's disease treated with subcutaneous apomorphine infusion or deep brain stimulation of the subthalamic nucleus. Issue 4 (16th March 2006) - De Gaspari, D; Siri, C; Landi, A; Cilia, R; Bonetti, A; Natuzzi, F; Morgante, L; Mariani, C B; Sganzerla, E; Pezzoli, G; Antonini, A
Abstract : Background: The clinical condition of advanced Parkinson's disease (PD) patients is often complicated by motor fluctuations and dyskinesias which are difficult to control with available oral medications. Objective: To compare clinical and neuropsychological 12 month outcome following subcutaneous apomorphine infusion (APO) and chronic deep brain stimulation of the subthalamic nucleus (STN-DBS) in advanced PD patients. Methods: Patients with advanced PD and medically untreatable fluctuations underwent either APO (13 patients) or STN-DBS (12 patients). All patients were clinically (UPDRS-III, AIMS, 12 h on-off daily) and neuropsychologically (MMSE, Hamilton-17 depression, NPI) evaluated at baseline and at 12 months. APO was discontinued at night. Results: At 12 months APO treatment (74.78±24.42 mg/day) resulted in significant reduction in off time (−51%) and no change in AIMS. Levodopa equivalent medication doses were reduced from 665.98±215 mg/day at baseline to 470±229 mg/day. MMSE, NPI, and Hamilton depression scores were unchanged. At 12 months STN-DBS resulted in significant clinical improvement in terms of reduction in daily off time (−76%) and AIMS (−81%) as well as levodopa equivalent medication doses (980±835 to 374±284 mg/day). Four out of 12 patients had stopped oral medications. MMSE was unchanged (from 28.6±0.3 to 28.4±0.6). Hamilton depression was also unchanged, but NPI showed significant worsening (from 6.58±9.8 to 18.16±10.2; p<0.02). Category fluency also declined. Conclusions: Both APO and STN-DBS resulted in significant clinical improvement in complicated PD. STN-DBS resulted in greater reduction in dopaminergic medications and provided 24 h motor benefit. However, STN-DBS, unlike APO, appears to be associated with significant worsening on NPI resulting from long term behavioral problems in some patients.